Excitation of the accelerating field by high-current electron beam in a periodic magnetic field - Onishchenko, I.N.; Sotnikov, G.V (Вопросы атомной науки и техники, 2004)
The excitation of a slow electromagnetic wave by intense relativistic electron beam (IREB) in the cylindrical
drift chamber is theoretically investigated. The beam current is modulated in time. Because of propagation of the
electron beam in the periodic magnetic field its surface is modulated in the longitudinal direction. Expressions for
the amplitude of the accelerating field are obtained, its dependences on parameters of an electron beam (depth of
spatial and of temporary modulation, period of modulation) is investigated. The radial structure of longitudinal components of an electromagnetic field of a slow wave and a possibility of acceleration of ions in the field of the excited
wave is analysed. Теоретично досліджується збудження повільної електромагнітної хвилі в циліндричному хвилеводі
потужнострумовим релятивістським електронним пучком при його транспортуванні в зовнішньому
періодичному магнітному полі. Отримано вираз для амплітуди подовжнього електричного поля. Досліджена
її залежність від параметрів електронного пучка (глибини просторової і часової модуляції, періоду
просторової модуляції). Аналізується радіальна структура електромагнітного поля повільної хвилі і
можливість прискорення іонів у полі збудженої повільної хвилі. Теоретически исследуется возбуждение медленной электромагнитной волны в цилиндрическом волноводе сильноточным релятивистским электронным пучком при его транспортировке во внешнем периодическом магнитном поле. Получены выражения для амплитуды продольного электрического поля, исследована
ее зависимость от параметров электронного пучка (глубины пространственной и временной модуляции, периода пространственной модуляции). Анализируется радиальная структура электромагнитного поля медленой волны и возможность ускорения ионов в поле возбужденной медленной волны.